Effectiveness of nutrition literacy intervention on pregnancy weight and eating behavior: a randomized controlled trial - Qian Li; Jie Wang (Scientific Reports)
Abstract This study aimed to evaluate the short-term (24 weeks of pregnancy) and long-term (pre-delivery) effects of a 12-week comprehensive nutritional literacy intervention (from week 12 to 24 of pregnancy) on pregnant women’s dietary behavior and weight. A pre-registered, two-arm, single-blind randomized controlled trial was conducted, enrolling 88 pregnant women at 12 weeks of gestation, who were randomly assigned to either the control group or the intervention group. Both groups received routine obstetric care, while the intervention group additionally received a 12-week personalized dietary intervention guided by Nutbeam’s health literacy framework.The intervention was tailored based on nutritional literacy assessments and lasted until 24 weeks of gestation. The primary outcome measures were nutrition literacy, restrained eating behavior, emotional eating behavior, and external eating behavior before delivery. Secondary outcomes included dietary balance indices and gestational weight gain. A total of 83 participants completed the analysis. The comprehensive dietary intervention significantly improved the overall nutritional literacy of pregnant women before delivery (51.00 ± 6.08 vs. 44.88 ± 6.34, P < 0.001), with significant improvements in knowledge literacy (31.75 ± 3.36 vs. 27.96 ± 3.92, P < 0.001) and behavioral literacy (6.77 ± 2.85 vs. 5.59 ± 2.54, P = 0.024). In terms of eating behavior, the intervention group had significantly higher scores for restrictive eating (32.90 ± 7.68 vs. 28.32 ± 8.24, P = 0.005) and external eating (32.57 ± 5.80 vs. 30.17 ± 5.93, P = 0.033) compared to the control group. The dietary quality index showed significant improvements in the intervention group in areas such as organ meats (P < 0.001), seafood (P = 0.01), algae (P = 0.008), nuts (P < 0.001), dairy products (P < 0.001), water intake (P < 0.001), and food variety (P < 0.001). Furthermore, the intervention group experienced significantly less weight gain during pregnancy than the control group (13.21 ± 3.61 kg vs. 16.18 ± 4.70 kg, P = 0.002). The comprehensive nutritional literacy intervention implemented in early pregnancy significantly improved pregnant women’s nutritional literacy levels in both the short and long term, optimized dietary behaviors, improved dietary quality, and effectively controlled weight gain during pregnancy. The study protocol follows the CONSORT guidelines and has been registered with the Chinese Clinical Trial Registry (ChiCTR2300075082).